Formation and Characterisation of the Silver Hydride Nanocluster Cation [Ag3H2((Ph2P)2CH2)]+ and Its Release of Hydrogen. Issue 50 (16th October 2014) - Girod, Marion; Krstić, Marjan; Antoine, Rodolphe; MacAleese, Luke; Lemoine, Jérome; Zavras, Athanasios; Khairallah, George N.; Bonačić‐Koutecký, Vlasta; Dugourd, Philippe; O'Hair, Richard A. J.
Abstract Multistage mass spectrometry and density functional theory (DFT) were used to characterise the small silver hydride nanocluster, [Ag3H2L]+ (where L=(Ph2P)2CH2) and its gas‐phase unimolecular chemistry. Collision‐induced dissociation (CID) yields [Ag2HL]+ as the major product while laser‐induced dissociation (LID) proceeds via H2 formation and subsequent release from [Ag3H2L]+, giving rise to [Ag3L]+ as the major product. Deuterium labelling studies on [Ag3D2L]+ prove that the source of H2 is from the hydrides and not from the ligand. Comparison of TD‐DFT absorption patterns obtained for the optimised structures with action spectroscopy results, allows assignment of the measured features to structures of precursors and products. Molecular dynamics "on the fly" reveal that AgH loss is favoured in the ground state, but H2 formation and loss is preferred in the first excited state S1, in agreement with CID and LID experimental findings. This indicates favourable photo‐induced formation of H2 and subsequent release from [Ag3H2L]+, an important finding in context of metal hydrides as a hydrogen storage medium, which can subsequently be released by heating or irradiation with light.